Habituation of Dhuha Prayer in Strengthening Early Childhood Piety at Raudhatul Athfal - Taranisa Baroro Purbo; Fajar Syarif; Muh. Ubaidillah Al Ghifary (Universitas Islam negeri Mahmud Yunus Batusangkar, 2025)
Moral education in early childhood plays a crucial role in shaping character, spiritual awareness, and lifelong religious commitment. One effective approach within Islamic education is the habituation of daily worship practices to internalize moral values from an early age. This study aims to examine how the habituation of Dhuha Prayer contributes to strengthening individual piety among early childhood learners. Using a qualitative approach with a phenomenological perspective, the research explores children’s lived experiences and the educational strategies implemented by teachers and parents. Data were collected through observation, in-depth interviews, documentation, and developmental assessment records involving principals, teachers, parents, and children aged 4–6 years. The findings indicate that consistent Dhuha Prayer practice, supported by teacher role modeling, structured religious routines, and active parental involvement, significantly enhances children’s spiritual awareness, discipline, emotional regulation, and positive social behavior. Religious habituation fosters piety not merely as ritual compliance but as an internalized moral character reflected in daily actions. Although challenges arise from developmental characteristics and diverse family backgrounds, adaptive strategies such as creative learning methods and intensive school–parent communication strengthen program effectiveness. The study concludes that integrating Dhuha Prayer habituation within an Islamic character-based curriculum is an effective strategy for fostering early childhood moral development and individual piety.